2010
DOI: 10.1002/app.33287
|View full text |Cite
|
Sign up to set email alerts
|

Optical properties of modified epoxy resin with various oxime derivatives in the UV‐VIS spectral region

Abstract: Optical absorbance measurements have been performed on the epoxy resin and the composites prepared by its modification with two different oxime derivatives (benzaldoxime and 2-furaldoxime) in the wavelength interval of 190-680 nm by unpolarized light. Using the experimental absorbance data, dielectric constant and refractive index dispersion have been determined by means of standard oscillator fit procedure. Moreover, based on the dispersion analysis, direct and indirect band gap energies of the samples have b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
17
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 18 publications
3
17
0
Order By: Relevance
“…The higher band gap (E g2 ) at around 3.50 eV, attributed to the p-p* transition of the benzene group in the epoxy backbone, which is also shown in the pure epoxy sample, is very close to the reported 3.45 eV. 87 On the other hand, the E g1 with a lower value associated with the band transition of PPy nanollers is observed to decrease with increasing the loading of PPy. The protons of the doped acid in the PPy nanollers can react with epoxy more easily to form hydroxyl groups 88 due to the more electronegative nature of oxygen than nitrogen.…”
Section: Bandgap Of Cured Nanocompositessupporting
confidence: 73%
“…The higher band gap (E g2 ) at around 3.50 eV, attributed to the p-p* transition of the benzene group in the epoxy backbone, which is also shown in the pure epoxy sample, is very close to the reported 3.45 eV. 87 On the other hand, the E g1 with a lower value associated with the band transition of PPy nanollers is observed to decrease with increasing the loading of PPy. The protons of the doped acid in the PPy nanollers can react with epoxy more easily to form hydroxyl groups 88 due to the more electronegative nature of oxygen than nitrogen.…”
Section: Bandgap Of Cured Nanocompositessupporting
confidence: 73%
“…These renewable natural resources also hold additional advantages being nontoxic, biodegradable, and therefore environmentally benign. Epoxy resin is a crosslinked thermoset polymer characterized by a wide range of desirable end properties such as excellence resistant to chemicals and good thermal stability [3][4][5][6][7][8][9]. As such, epoxy resin is widely used for applications such as coating, adhesive and matrices for composite materials.…”
Section: Introductionmentioning
confidence: 99%
“…benzaldoxime and 2-furaldoxime) in the UV-vis region (particularly from 190 nm to 680 nm wavelength) have been investigated in a recent paper (Durmus et al, 2011). The experimental results have shown that oxime derivatives have not caused strong changes in the refractive index of the resin, but optical band energies greatly increase by modification.…”
Section: 9mentioning
confidence: 96%